1996
DOI: 10.1210/endo.137.9.8756585
|View full text |Cite
|
Sign up to set email alerts
|

The human osteoclast precursor circulates in the monocyte fraction.

Abstract: The osteoclast is known to be formed by fusion of circulating mononuclear precursor cells of haematopoietic origin. The precise nature of these circulating cells and, in particular, their relation to monocytes is unknown. We have developed an in vitro system of human osteoclast formation whereby human monocytes [CD14, CD11a, CD11b and HLA-DR positive, and tartrate-resistant acid phosphatase (TRAP), calcitonin receptor (CTR), vitronectin receptor (VNR) negative] were isolated and cocultured for up to 21 days wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
199
2
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 289 publications
(215 citation statements)
references
References 8 publications
13
199
2
1
Order By: Relevance
“…A previous study [3] suggested that osteoclast precursors are present in the circulation of osteopetrotic mice. Moreover, avian [4], murine [5,6] and human [7][8][9] monocytes in the peripheral blood can differentiate into osteoclast-like cells.…”
Section: Osteoclastsmentioning
confidence: 99%
“…A previous study [3] suggested that osteoclast precursors are present in the circulation of osteopetrotic mice. Moreover, avian [4], murine [5,6] and human [7][8][9] monocytes in the peripheral blood can differentiate into osteoclast-like cells.…”
Section: Osteoclastsmentioning
confidence: 99%
“…Osteoclast precursors had clearly been shown to be present in peripheral blood [11]; while circulating osteoblast precursors, identified on the basis of adherence to plastic, had also been found by several groups [12,13], the concentration of these cells was extremely low (~1 in 10 8 mononuclear cells [MNCs] or less in humans) [13]. We reasoned that plastic adherence may well have underestimated the concentration of these cells in peripheral blood, and using flow cytometry following staining with OCN or AP antibodies, recently demonstrated that OCN pos or AP pos cells were indeed present in the peripheral blood in humans, constituting ~1% of circulating MNCs [14].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It exhibits a number of specialised cytochemical and functional features, including the ability to carry out lacunar bone resorption. Increased osteoclast formation and activity is seen in a number of osteolytic bone and joint conditions, including notably giant cell tumour of bone (GCTB), a primary bone tumour, which contains numerous, very large, often hyper-nucleated osteoclastic giant cells that effect a considerable amount of bone resorption.…”
mentioning
confidence: 99%